(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
Taxonomic revision and morphometrics are two crucial facets for the proper identification, updating of taxa, and strengthening phenetic relationships of angiosperms. This study focused on the systematics and morphometrics of the subfamily Byttnerioideae Burnett (Family Malvaceae) for the first time in Bangladesh, revealing eight taxa under seven genera, namely Abroma Jacq., Ayenia L., Guazuma Mill., Kleinhovia L., Melochia L., Theobroma L. and Waltheria L. These seven genera fall into three tribes: Byttnerieae, Theobromateae, and Hermannieae. Dichotomous bracketed keys to genera and species were generated. Detailed nomenclature, diagnostic characteristics, illustrations, representative specimens, notes on distribution and uses for each species were provided. Morphometrics study was conducted employing cluster and principal components analysis (PCA). Cluster analysis revealed close relationships between Theobromateae and Hermannieae tribes compared to Byttnerieae tribe in the form of UPGMA dendrogram. Similarity matrix revealed the highest affinity between Ayenia elegans Ridl. and Ayenia grandifolia (DC.) Christenh. & Byng. In the PCA analysis, the first two principal components explained approximately 82.26% cumulative variance. PCA-derived scatter and projection plots supported the topology and inter-relationships in the cluster analysis. These findings will enhance future conservation strategies, especially for the threatened and medicinally important taxa of Byttnerioideae in Bangladesh, and support molecular phylogenetic studies of the subfamily Byttnerioideae. Bangladesh J. Plant Taxon. 31(1): 123-140, 2024 (June)